The effect of psychological richness on the meaning in life of college students: the chain mediating effect of sense of coherence and self-compassion - He, Qingsen; Chen, Yixin; Cao, Shan (Frontiers in Psychology, 2025)
BackgroundPsychological richness is an important factor affecting the meaning in life of college students. Although previous studies have confirmed the association between psychological richness and meaning in life, its mechanism remains unclear.ObjectiveThis study aimed to examine the relationship between psychological richness and the meaning in life of college students, and the chain mediating role of the sense of coherence and self-compassion in such a relationship.MethodsThis study surveyed 2,671 college students in Henan Province, China, using the Psychologically Rich Life Questionnaire, Sense of Coherence Scale, Self-Compassion Scale-Short Form, and Meaning in Life Questionnaire.Results(1) Psychological richness was significantly correlated with sense of coherence (r = 0.385, p < 0.001), self-compassion (r = 0.439, p < 0.001), and meaning in life (r = 0.296, p < 0.001); sense of coherence was correlated with self-compassion (r = 0.478, p < 0.001) and meaning in life (r = 0.375, p < 0.001); self-compassion was correlated with the meaning in life (r = 0.402, p < 0.001); (2) The mediating effect analysis showed that the mediating effect of sense of coherence (95%CI: 0.060 0.104), self-compassion (95%CI: 0.056 0.100) and the chain mediating effect of sense of coherence and self-compassion (95%CI: 0.026 0.047) were significant.ConclusionPsychological richness can not only directly predict college students’ meaning in life, but also indirectly predict their meaning in life through the chain mediating effect of sense of coherence and self-compassion. This research provides valuable suggestions for universities, which will help them adjust their mental health education policies and provide a solid scientific basis for enhancing the sense of meaning in life and improving the mental health status of college students.